2010
DOI: 10.5539/ijms.v2n1p65
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Perceptions, Attitudes and Willingness to Pay towards Food Products with “No Added Msg” Labeling

Abstract: This research was carried out in order to determine consumers' perceptions, attitudes and willingness-to-pay (WTP) towards food products with "No Added MSG" labeling. A total of 200 respondents within the area of Klang Valley were interviewed using a close-ended questionnaire. The Contingent Valuation Method (CVM) was used to determine the consumers' WTP for the consumption of safer beef. A logit model was used to estimate the premium that consumers are willing to pay for food products with "No Added MSG" labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 37 publications
2
27
3
1
Order By: Relevance
“…However, Radam et al . () and Neill () reported that the premium was estimated to be from USD 0.11 to 0.60 per container, which are larger than our estimate (USD 0.09).…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…However, Radam et al . () and Neill () reported that the premium was estimated to be from USD 0.11 to 0.60 per container, which are larger than our estimate (USD 0.09).…”
Section: Resultscontrasting
confidence: 82%
“…(), Barnard & Mitra (), Radam et al . (), Neill () and Salladarré et al . () have employed the CV method to valuing the consumers’ preference for EFPs.…”
Section: Methodsmentioning
confidence: 95%
“…Perceptions represent the formation of an individual state of mental awareness that is affected by internal and external environmental stimuli such as economic, social, and cultural influences (Radam et al 2010). The survey results suggest that the respondents considered food poisoning, spoilage, and additives as the most important hazards to dairy products (Table 2).…”
Section: Risk Awareness Perceptions and Attitudes On Food Safetymentioning
confidence: 94%
“…Seseorang yang berumur relatif muda, akan lebih cepat menerima sesuatu yang baru. Selain itu, sebagian besar pengambilan keputusan pembelian beras dilakukan oleh ibu rumah tangga karena menurut Radam et al (2010), bahwa perempuan lebih sadar kesehatan dibandingkan dengan laki-laki dan jumlah anggota keluarga 4 atau lebih cenderung sensitif terhadap harga dan enggan membayar produk yang tidak menjadi prioritasnya dan beras merupakan makanan utama yang harus dipilih dan dikonsumsi sesuai dengan kebutuhan keluarga.…”
Section: Pendahuluanunclassified